Combination of Lactobacillus acidophilus and Bifidobacterium animalis subsp. lactis Shows a Stronger Anti-Inflammatory Effect than Individual Strains in HT-29 Cells - Li, Sing-Chung (Nutrients, 2019)
Inflammatory bowel disease (IBD) is an emerging health problem associated with the dysregulation of the intestinal immune system and microbiome. Probiotics are able to reduce inflammatory responses in intestinal epithelial cells (IECs). However, entire signaling pathways and the interaction between different probiotics have not been well-documented. This study was designed to investigate the anti-inflammatory effects and mechanisms of single and combined probiotics. HT-29 cells were induced by lipopolysaccharide (LPS) and tumor necrosis factor (TNF)-α, treated with Lactobacillus acidophilus, Bifidobacterium animalis subsp. lactis or their combination and analyzed for inflammation-related molecules. Both L. acidophilus and B. animalis subsp. lactis reduced interleukin (IL)-8 secretion and the expressions of phosphorylated p65 nuclear factor-kappa B (p-p65 NF-κB), phosphorylated p38 mitogen-activated protein kinase (p-p38 MAPK), vascular cell adhesion molecule-1 (VCAM-1) and cyclooxygenase-2 (COX-2), while they increased toll-like receptor 2 (TLR2) expression. L. acidophilus did not decrease intercellular adhesion molecule-1 (ICAM-1) but enhanced the inhibitory efficacy of B. animalis subsp. lactis. Combined probiotics showed the best anti-inflammatory activity. These results suggest that L. acidophilus and B. animalis subsp. lactis may exert a potent anti-inflammatory effect through modulating TLR2-mediated NF-κB and MAPK signaling pathways in inflammatory IECs. Both strains, especially their combination, may be novel adjuvants for IBD therapy.